La difficile gestion globale de l’eau en Camargue (France) : le Contrat de delta - Alain Dervieux (VertigO)
In the Camargue, water is a major link between human activities and ecosystems. Rice growing, being the most important agricultural activity, has been at the head of the hydraulic networks for more than 50 years. Being the main reason for the introduction of important volumes of fresh water from the River Rhone into the Camargue during the dry season, a ressource, which in turn, is made available for other human activities: nature conservation, tourism, breeding, hunting and fishing. This situation has contributed to the modification of the region's natural hydrological rhythms that were once marked by dry Mediterranean summers. The result is an increasingly complex system that requires a water management programme that can meet both National and European objectives for sustainable development.Conservation plays a large role in today's land and water management policies, but there are other considerations essential to ensuring the durability of the region's development. The Contract of the Camargue Delta project must manage the use and allocation of fresh-water with mutual respect for the different beneficiaries while collectively respecting the many natural environments on which a good part of the territory's economy depends (tourism, grazing, hunting, fishing…). All of which are indispensable in maintaining the biodiversity of the delta.This project, carried out by the Regional Natural Park of the Camargue, aims to improve upon current water management policy for the benefit of the local population whiled striving to conserve this resource, protect the ecosystem, and develop the local economy. To do this, the project must overcome strong and sometimes contradictory tensions between political engines, social and cultural heritages, in a region where the advancement of flood prevention is strongly required, with a coherent and shared vision of water management.In conclusion, whatever the consequences of the management system on the ecosystems in terms of biodiversity, today water is present all year round in the Camargue and has become an essential characteristic of the landscape.